Evaluation of Industrial Field Practice Program using the Tyler Model in the Informatics Engineering Education Department - Yunus, Yuliawati; Ambiyar, Ambiyar; Rizal, Fahmi (Universitas Pendidikan Mandalika, 2024)
This research aims to describe the evaluation implementation of industrial field practices in the informatics engineering education study program, Faculty of Teacher Training and Education, Universitas Putra Indonesia